Pengaaruh PBL dan Pengelolaan Kelas Terhadap Kemandirian dan Tanggung Jawab Siswa SD - Rifki Ansori (Universitas Muhammadiyah Surabaya, 2026)
his study aims to analyze the impact of Problem-Based Learning (PBL) and classroom management on independence and responsibility of students at SDN Banjarkemanten II Buduran Sidoarjo. The research method used is a quasi-experimental design with a pre-test post-test control group design. The sample consisted of 56 fifth-grade students, divided into two groups: the experimental group, which used PBL and effective classroom management, and the control group, which used conventional teaching methods. Data were collected through questionnaires to measure student independence and responsibility, and analyzed using the t-test to examine differences between groups. The results show that the application of PBL and effective classroom management significantly influenced independence (t = 3.21, p = 0.002) and responsibility (t = 2.89, p = 0.005) in students. The findings indicate that students in the PBL and classroom management group demonstrated higher levels of independence and responsibility compared to those using conventional teaching methods. Therefore, it is recommended that PBL be more widely implemented in elementary schools, supported by structured classroom management, to optimally develop student character.